Macromol. Rapid Commun. 3/2018. Issue 3 (1st February 2018) - Sakai, Shinji; Ueda, Kohei; Gantumur, Enkhtuul; Taya, Masahito; Nakamura, Makoto
Abstract : Front Cover : Horseradish‐peroxidase‐catalyzed hydrogelation is combined with inkjet bioprinting technology for fabricating 3D cell‐laden hydrogel constructs. The constructs are obtained by sequentially dropping a bioink containing hydrogen peroxide onto droplets of another bioink containing the enzyme and cells. Further details can be found in article number1700534 by Shinji Sakai and co‐workers.